Sirkulasi Sosiologis dan Psikologis dalam Fenomena Bullying di Pesantren - Mokhamad Miptakhul Ulum (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2021)
Bullying has two different perceptions in pesantren. Firstly, bullying is something tense, stressful, containing an element that is very hard, extreme. Pesantren as educational institutions that educate students morals has immoral actions that to fatal. Secondly, bullying has goodwill, to practice independence, heart constancy of students in pesantren. Bullying words or actions that normally (mild bullying) don’t mean to be criminal but based on to strengthen the relationship of brotherhood so that mentally strengthen of students. This article is the result of the author’s thought who observes of the reality that bullying culture circulation at in pesantren. A systematic reflection is an approach for the author in making this research. The author analyzes that the circulation of sociological is the action or verbal bullying in pesantren is can has a positive impact that is growing the power mental of students. However, that psychologically bullying in pesantren has a negative impact that is something very fatal like depression, stress, and other ugliness.